Phosphorus-doped hydrothermal synchronously-activated hierarchical-pore green biochar, preparation method thereof and application of phosphorus-doped hydrothermal synchronously-activated hierarchical-pore green biochar in formaldehyde adsorption

By introducing phosphoric acid catalyst and potassium hydroxide activation treatment in the hydrothermal stage, a phosphorus-doped biochar with a multi-level pore structure was constructed, which solved the problems of limited formaldehyde adsorption selectivity and capacity of biochar materials and achieved efficient formaldehyde removal.

CN120586831AInactive Publication Date: 2025-09-05JILIN JIANZHU UNIVERSITY

Patent Information

Application Number
CN202511114264.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2025-09-05
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing biochar materials have problems such as uneven pore structure distribution, low surface functional group content and weak polarity selectivity, which leads to limited adsorption selectivity and capacity for formaldehyde. Traditional phosphorus doping methods have problems such as uneven phosphorus distribution and pore structure destruction.

Method used

By introducing a phosphoric acid catalyst to carry out a carbonization reaction in the hydrothermal stage and combining it with potassium hydroxide activation treatment, a multi-level pore structure is constructed, achieving uniform doping of phosphorus elements and coordinated regulation of the pore structure, forming highly dispersed active sites and abundant phosphorus doping sites, and enhancing the chemical adsorption capacity of formaldehyde.

Benefits of technology

The pore structure regulation ability and adsorption performance of biochar have been significantly improved, achieving efficient removal of formaldehyde. The material has a high specific surface area, rich phosphorus-containing functional groups and good adsorption stability, and is suitable for indoor air purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120586831A_ABST
    Figure CN120586831A_ABST
Patent Text Reader

Abstract

The invention provides phosphorus-doped hydrothermal synchronously-activated hierarchical pore green biochar, a preparation method thereof and application of the phosphorus-doped hydrothermal synchronously-activated hierarchical pore green biochar in formaldehyde adsorption, and belongs to the technical field of biomass resource high-value utilization and air pollution control. The preparation method comprises the following steps: mixing a biomass raw material with a phosphoric acid catalyst, carrying out hydrothermal carbonization reaction, carrying out solid-liquid separation on a reaction product after the reaction is finished, collecting a solid-phase material, drying, mixing with potassium hydroxide, activating, washing and drying the obtained product, and thus obtaining the phosphorus-doped hydrothermal synchronously-activated hierarchical porous green charcoal. Phosphoric acid is introduced in the hydrothermal stage to serve as a structure-directing agent and a doping source, uniform doping of phosphorus and coordinated regulation and control of a pore structure are achieved, a hierarchical pore channel system is formed in the subsequent activation process, and the physical adsorption and chemical fixation capacity of the biochar to formaldehyde molecules is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-value utilization of biomass resources and air pollution control, and in particular relates to a phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar, a preparation method thereof, and an application thereof in formaldehyde adsorption. Background Art

[0002] In recent years, with the acceleration of urbanization and the improvement of residents' quality of life, indoor air quality has received increasing attention. Formaldehyde, a typical indoor pollutant, primarily originates from building decoration materials, wood-based panels, furniture, and adhesives. Its long-term, low-concentration release and continuous volatility pose a potential threat to human health. Research has shown that formaldehyde is highly allergenic and carcinogenic, and long-term exposure can induce respiratory diseases, neurological disorders, and even leukemia. Therefore, the development of efficient, green, and sustainable formaldehyde-purification materials has become a key research direction in the environmental protection field.

[0003] Among the many technologies for formaldehyde removal, physical adsorption is highly favored due to its ease of operation, low cost, and lack of secondary pollution. Among them, porous carbon materials prepared from biomass have become a hot topic in gas adsorption material research due to their renewable raw material availability, environmental friendliness, and abundant surface active sites. Compared to traditional activated carbon, biochar offers advantages in terms of resource availability, environmental impact, and structural control, making it particularly suitable for developing green material systems for indoor air purification. However, conventional biochar materials commonly suffer from uneven pore structure distribution, low surface functional group content, and weak polarity selectivity, which limits their adsorption selectivity and capacity for polar small molecules such as formaldehyde (HCHO). In particular, an inappropriate micropore-to-mesopore ratio can hinder transport, reducing adsorption rate and saturation capacity. While narrower micropores can significantly enhance adsorption capacity, a narrow micropore structure alone is insufficient to significantly improve performance. Therefore, the key to this research lies in the coordinated regulation of biochar pore structure and surface functional groups.

[0004] To enhance the structural and functional properties of biochar, researchers have recently attempted to functionalize carbon materials by introducing heteroatom doping. Phosphorus doping has garnered widespread attention due to its unique electronic effects and structural guidance. Phosphorus atoms can induce graphite edge defects, regulate π electron distribution, and enhance the polarity of the carbon skeleton in carbon materials, thereby improving their adsorption capacity for polar molecules such as formaldehyde. Furthermore, phosphorus itself can participate in a variety of adsorption mechanisms, such as Lewis acid-base neutralization, hydrogen bonding, and coordination adsorption, giving it strong selectivity and affinity. Traditional phosphorus doping methods generally employ pre-impregnation or post-doping methods, mixing phosphoric acid or a phosphorus source solution with the carbon material. However, these methods present problems such as uneven phosphorus distribution, low doping efficiency, and pore structure destruction.

[0005] In addition, some scholars have also improved the performance of carbon materials through activation. The KOH activation method is considered to be one of the most effective chemical activation methods because it undergoes multiple gas-solid and liquid-solid reactions with carbon precursors at high temperatures, which can effectively generate micropores, mesopores and some macroporous structures. KOH reacts with carbon to form intermediate products such as K, K2CO3, K2O, and CO2. These gases and liquids have an etching effect on the carbon skeleton and can form developed multi-level pores inside the carbon material, which is conducive to the rapid diffusion and enrichment of the target gas. However, traditional KOH activation still has problems such as uneven pore size distribution, structural collapse, and loss of doping elements, and needs to be optimized in conjunction with the doping mechanism.

[0006] Therefore, in order to achieve efficient removal of indoor formaldehyde, the present invention proposes a phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar and a preparation method thereof. Summary of the Invention

[0007] In order to solve the above technical problems, the present invention proposes a phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar, its preparation method and application in formaldehyde adsorption. By introducing a phosphoric acid catalyst and optimizing the process flow, partial activation is completed while constructing the skeleton structure in the hydrothermal stage, thereby significantly improving the pore structure regulation ability and adsorption performance of the product.

[0008] To achieve the above objectives, the present invention provides the following technical solutions:

[0009] One of the technical solutions of the present invention:

[0010] A method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar comprises the following steps:

[0011] The biomass raw material is mixed with a phosphoric acid catalyst to carry out a hydrothermal carbonization reaction. After the reaction is completed, the reaction product is separated into solid and liquid. The solid phase material is collected, dried, and then mixed with potassium hydroxide for activation treatment. The obtained product is washed and dried to obtain the phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar.

[0012] Beneficial effects: Phosphoric acid, as a structure regulator and doping source, participates in the construction of the carbon skeleton in the early stage of hydrothermal carbonization, so that the phosphorus element is uniformly embedded in the carbon lattice in the form of CPO, C3-P=O, etc., forming highly dispersed active sites. The hydrothermal environment promotes the hydrolysis and polymerization of biomass cellulose and hemicellulose, generating a carbon precursor rich in micropores, providing a basic skeleton for subsequent KOH activation. At high temperature, KOH reacts with carbon to generate K2CO3 and H2 gas, which form hierarchical pores (micropores-mesopores-macropores) through etching and pore expansion, increasing the specific surface area. The multi-level pore structure provides fast mass transfer channels (macropores / mesopores) and high specific surface area (micropores), and the acidic sites introduced by phosphorus doping (such as P=O, P-OH) enhance the chemical adsorption of formaldehyde through hydrogen bonds, electrostatic interactions and chemical reactions (such as nucleophilic addition).

[0013] Furthermore, the mass ratio of the biomass raw material to the phosphoric acid catalyst is 1:9, and the concentration of the phosphoric acid catalyst is 1 mol / L.

[0014] Beneficial Effects: Phosphoric acid acts as a dehydrating agent, promoting deep carbonization of biomass. It also serves as a phosphorus source, enabling high doping levels. High phosphoric acid concentrations (1 mol / L) disrupt the biomass hydrogen bond network through protonation, generating more activated carbon precursors and providing a material foundation for subsequent pore formation. High phosphorus doping increases the density of surface acidic sites, enhancing the chemical adsorption capacity for formaldehyde. The microporous structure formed by phosphoric acid catalysis provides the primary adsorption space, synergizing with the mesopores generated by KOH activation to achieve integrated "adsorption-diffusion" processes.

[0015] Furthermore, the reaction temperature of the hydrothermal carbonization reaction is 200-240° C., the reaction time is 2 h, and the hydrothermal carbonization reaction is carried out under a nitrogen atmosphere with a nitrogen flow rate of 60 mL / min.

[0016] Beneficial effects: The hydrothermal temperature of 200-240°C causes moderate carbonization of the biomass, generating microporous carbon microspheres; the 2-hour reaction time ensures sufficient carbonization but avoids excessive condensation that could lead to pore blockage; the nitrogen atmosphere (60 mL / min) inhibits oxidation reactions, maintains the integrity of the carbon skeleton, and promotes in-situ doping of phosphorus species generated by the decomposition of phosphoric acid. The hydrothermally generated micropores provide a template for KOH activation, forming a richer mesoporous network after etching, thereby increasing the diffusion rate of formaldehyde molecules; the phosphorus doping sites are anchored in the carbon skeleton during the hydrothermal stage, avoiding uneven doping during post-processing.

[0017] Furthermore, the mass ratio of potassium hydroxide to solid phase material is 1:3 (here refers to the dry mass of the solid phase material), the temperature of the activation treatment is 700°C, the reaction time is 2h, the heating rate is 5°C / min, and the activation treatment is carried out under a nitrogen atmosphere with a nitrogen flow rate of 60mL / min.

[0018] Beneficial Effects: A KOH to solid material mass ratio of 1:3 balances etching intensity and carbon loss, preventing structural collapse caused by overactivation. A high temperature of 700°C and a heating rate of 5°C / min promote KOH melt penetration, resulting in a hierarchical structure dominated by micropores and supplemented by mesopores. A nitrogen atmosphere (60 mL / min) prevents carbon oxidation at high temperatures, ensuring pore structure stability. The micropores generated by KOH activation provide high adsorption capacity, while the mesopores accelerate the mass transfer of formaldehyde molecules within the pores, and the macropores act as a "reservoir" to buffer concentration fluctuations. Phosphorus-doped sites (e.g., C3-P=O) are further oxidized during activation, forming stronger Lewis acidic sites that undergo acid-base neutralization or condensation reactions with the carbonyl group (-CHO) of the formaldehyde molecule, generating a stable adsorbed product.

[0019] More specifically, a method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar comprises the following steps:

[0020] (1) Dry and remove impurities from biomass raw materials (such as sawdust, agricultural and forestry waste, etc.), mechanically crush them, and obtain powdered materials with uniform particle size through screening for use;

[0021] (2) The pretreated biomass raw material and 1 mol / L phosphoric acid solution (as a phosphorus source and acid catalyst) were added to a high-pressure closed hydrothermal reactor and stirred to form a uniform slurry;

[0022] (3) The reactor was purged with nitrogen to remove air from the system and avoid oxidation interference. The temperature was then raised to the set temperature (200-240°C) and maintained for a certain reaction time (2 h). The hydrothermal carbonization reaction was completed under magnetic stirring (175-185 rad / min).

[0023] (4) After the reaction is completed, the product is naturally cooled to room temperature and recovered by solid-liquid separation;

[0024] (5) The dried hydrothermal product is fully dry-mixed with potassium hydroxide (KOH) according to a mass ratio and stirred evenly to prepare a pre-activated mixture;

[0025] (6) The pre-activated mixture is placed in a nitrogen-filled tube furnace, heated to a set temperature (700°C) under a nitrogen atmosphere and kept at this temperature for a certain period of time to achieve chemical activation of the pore structure;

[0026] (7) After the activation reaction is completed, the product is washed with a large amount of deionized water until the pH value is close to neutral, and the resulting solid sample is finally dried to obtain the finished product of phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar.

[0027] The second technical solution of the present invention:

[0028] A phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar is prepared according to the preparation method.

[0029] The third technical solution of the present invention:

[0030] An application of the phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar in formaldehyde adsorption.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] This method introduces phosphoric acid as a structure-directing agent and doping source during the hydrothermal stage, achieving uniform phosphorus doping and coordinated regulation of pore structure. This creates a multi-level pore channel system during the subsequent activation process, significantly enhancing the biochar's ability to physically adsorb and chemically fix formaldehyde molecules. This method is simple, highly controllable, and environmentally friendly. The resulting material possesses a high specific surface area, abundant phosphorus-containing functional groups, and excellent adsorption stability, making it suitable for applications in indoor air purification and environmental remediation. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings, which constitute part of the present invention, are provided to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are provided to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:

[0034] Figure 1 N2 adsorption-desorption isotherms of the biochar materials of Examples 1-2 and Comparative Examples 1-2;

[0035] Figure 2 HCHO breakthrough curves of the biochar materials of Examples 1-2 and Comparative Examples 1-2 measured under drying conditions at 25°C. DETAILED DESCRIPTION

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be exemplary only.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0041] The present invention provides a method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar, comprising the following steps:

[0042] The biomass raw material is mixed with a phosphoric acid catalyst to carry out a hydrothermal carbonization reaction. After the reaction is completed, the reaction product is separated into solid and liquid. The solid phase material is collected, dried, and then mixed with potassium hydroxide for activation treatment. The obtained product is washed and dried to obtain the phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar.

[0043] In a preferred embodiment of the present invention, the mass ratio of the biomass raw material to the phosphoric acid catalyst is 1:9.

[0044] In a preferred embodiment of the present invention, the concentration of the phosphoric acid catalyst is 1 mol / L.

[0045] In a preferred embodiment of the present invention, the reaction temperature of the hydrothermal carbonization reaction is 200-240° C., and the reaction time is 2 hours.

[0046] In a preferred embodiment of the present invention, the hydrothermal carbonization reaction is carried out under a nitrogen atmosphere, and the flow rate of the nitrogen is 60 mL / min.

[0047] In a preferred embodiment of the present invention, the mass ratio of potassium hydroxide to solid phase material is 1:3.

[0048] In a preferred embodiment of the present invention, the activation treatment temperature is 700° C., the reaction time is 2 h, and the heating rate is 5° C. / min.

[0049] In a preferred embodiment of the present invention, the activation treatment is carried out under a nitrogen atmosphere, and the flow rate of the nitrogen is 60 mL / min.

[0050] More specifically, a method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar in an embodiment of the present invention comprises the following steps:

[0051] (1) Select well-dried wood chips, agricultural and forestry wastes (such as cypress sawdust) that are free of oil and impurities as carbon source raw materials. Dry the sawdust at 105°C for 12 hours to remove free water from the raw materials. Use a high-speed grinder to grind it into a fine powder. Then use a standard sieve to sieve and retain the part with a particle size of less than 180 μm (about 80 mesh) for later use.

[0052] (2) Weigh 10 g of the raw material obtained in step (1) and add it to a 250 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor. Add 90 mL of a 1 mol / L phosphoric acid (H3PO4) solution catalyst (the mass ratio of the biomass raw material to the phosphoric acid solution catalyst is 1:9). Phosphoric acid serves as a catalyst, structure-directing agent, and phosphorus doping source, and can simultaneously regulate the carbonization process and functional group formation.

[0053] (3) The mixture was stirred manually with a glass rod and then stirred at 300 rpm for 30 min using a magnetic stirrer to fully mix. The reactor was then sealed and purged with high-purity nitrogen (99.99%) at a flow rate of 60 mL / min for 15 min to exclude air and avoid interference with the oxidation reaction.

[0054] (4) The starting temperature of the reactor is room temperature, the pressure gauge should be controlled within the range of 1-5 MPa, the temperature setting range is 200-240 °C, the reaction time is set to 2 h, the heating rate is set to 10 °C / min, the reactor is operated and magnetic stirring is performed at a speed of 175-185 rad / min to carry out the hydrothermal carbonization reaction; during this process, phosphoric acid penetrates into the raw material, promotes the hydrolysis, rearrangement and carbonization of hemicellulose and cellulose, and realizes the in-situ doping of phosphorus element;

[0055] (5) After the hydrothermal carbonization reaction is completed, the reactor is naturally cooled to room temperature (about 20-25°C), the reactor cover is opened, the reaction mixture is taken out, and solid-liquid separation is performed by vacuum filtration. The filtrate is discarded, and the obtained wet solid hydrothermal carbon is retained. The solid residue is repeatedly washed 3-5 times with a large amount of deionized water until the pH of the washing liquid is close to neutral (6.5-7.5) to remove excess phosphoric acid and soluble by-products. The washed solid is dried at 80°C for 12 hours to obtain a preliminary phosphorus-doped hydrothermal carbon sample;

[0056] (6) The dried preliminary phosphorus-doped hydrothermal carbon sample and potassium hydroxide (KOH) were weighed in a mass ratio of 1:3 and placed in an agate mortar for thorough dry mixing. The stirring time was not less than 15 min to ensure that KOH was evenly coated on the surface of the hydrothermal carbon particles to form a homogeneous pre-activated system.

[0057] (7) The dry mixed sample was placed in a ceramic boat and sent to the constant temperature zone in the center of the tube furnace. During the activation process, nitrogen was continuously introduced (flow rate: 60 mL / min) to maintain an inert atmosphere to prevent oxidation of the carbon material. The heating rate was set at 5 °C / min from room temperature to 700 °C and kept at this temperature for 120 min to complete the carbon thermal activation reaction. KOH can undergo a series of complex gas-solid / liquid-solid reactions with the carbon material at high temperature, forming a large number of microporous and mesoporous structures, while synergistically enhancing the phosphorus doping effect.

[0058] (8) After cooling to room temperature, the reaction product was taken out and washed with deionized water several times until the pH of the washing solution stabilized at around 7. If necessary, 0.1 mol / L dilute hydrochloric acid solution could be used for pre-washing to remove residual K compounds (such as K2CO3 or K2O). The product was then rinsed with deionized water until neutral. The solid sample was finally dried under vacuum at 80 °C for 12 h to obtain the target product, which was phosphorus-doped hydrothermally activated hierarchical porous green biochar.

[0059] The embodiment of the present invention also provides a phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar, which is prepared according to the preparation method.

[0060] All raw materials used in the examples of the present invention were purchased from the market.

[0061] The technical solution of the present invention is further illustrated by the following examples.

[0062] Example 1

[0063] A method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar comprises the following steps:

[0064] (1) Select well-dried cypress sawdust without oil or impurities as the carbon source raw material. Dry the sawdust at 105°C for 12 hours to remove the free water in the raw material. Use a high-speed grinder to grind it into a fine powder. Then use a standard sieve to sieve it. Keep the part with a particle size less than 180 μm (about 80 mesh) for later use.

[0065] (2) Weigh 10 g of the cypress wood raw material obtained in step (1) and add it to a 250 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor. Add 90 mL of a 1 mol / L phosphoric acid (H3PO4) solution catalyst (the mass ratio of the biomass raw material to the phosphoric acid solution catalyst is 1:9). Phosphoric acid serves as a catalyst, structure-directing agent, and phosphorus doping source, and can simultaneously regulate the carbonization process and functional group formation.

[0066] (3) The mixture was stirred manually with a glass rod and then stirred at 300 rpm for 30 min using a magnetic stirrer to fully mix. The reactor was then sealed and purged with high-purity nitrogen (99.99%) at a flow rate of 60 mL / min for 15 min to exclude air and avoid interference with the oxidation reaction.

[0067] (4) The initial temperature of the reactor is room temperature, the pressure gauge is controlled at 5 MPa, the temperature is set to 200 °C, the reaction time is set to 2 h, the heating rate is set to 10 °C / min, the reactor is operated and magnetic stirring is performed at a speed of 180 rad / min to carry out the hydrothermal carbonization reaction; during this process, phosphoric acid penetrates into the raw material, promotes the hydrolysis, rearrangement and carbonization of hemicellulose and cellulose, and realizes the in-situ doping of phosphorus element;

[0068] (5) After the hydrothermal carbonization reaction is completed, the reactor is naturally cooled to room temperature, the reactor cover is opened, the reaction mixture is taken out, and the solid-liquid separation is performed by vacuum filtration. The filtrate is discarded, and the obtained wet solid hydrothermal carbon is retained. The solid residue is repeatedly washed 5 times with a large amount of deionized water until the pH of the washing liquid is close to neutral (7.5) to remove excess phosphoric acid and soluble by-products. The washed solid is dried at 80 ° C for 12 h to obtain a preliminary phosphorus-doped hydrothermal carbon sample;

[0069] (6) The dried preliminary phosphorus-doped hydrothermal carbon sample and potassium hydroxide (KOH) were weighed in a mass ratio of 1:3 and placed in an agate mortar for thorough dry mixing. The stirring time was not less than 15 min to ensure that KOH was evenly coated on the surface of the hydrothermal carbon particles to form a homogeneous pre-activated system.

[0070] (7) The dry mixed sample was placed in a ceramic boat and sent to the constant temperature zone in the center of the tube furnace. During the activation process, nitrogen was continuously introduced (flow rate: 60 mL / min) to maintain an inert atmosphere to prevent oxidation of the carbon material. The heating rate was set at 5 °C / min from room temperature to 700 °C and kept at this temperature for 120 min to complete the carbon thermal activation reaction. KOH can undergo a series of complex gas-solid / liquid-solid reactions with the carbon material at high temperature, forming a large number of microporous and mesoporous structures, while synergistically enhancing the phosphorus doping effect.

[0071] (8) After cooling to room temperature, the reaction product was taken out and washed with deionized water several times until the pH of the washing solution stabilized at 7. The solid sample was finally dried in vacuum at 80 °C for 12 h to obtain the target product, which was phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar (denoted as MBP2-200-A).

[0072] Example 2

[0073] The same as Example 1, except that in step (4), the temperature of the reactor was set to 240°C, and the obtained product was recorded as MBP2-240-A.

[0074] Comparative Example 1

[0075] Same as Example 1, except that 110 mL of a 1 mol / L phosphoric acid (H3PO4) solution catalyst was added (at this time, the mass ratio of the biomass raw material to the phosphoric acid solution catalyst was 1:11), and the resulting product was denoted as MBP3-240-A.

[0076] Comparative Example 2

[0077] Same as Example 1, except that the steps of hydrothermal carbonization, phosphorus doping and activation were omitted. The steps of phosphorus doping were as follows:

[0078] Select well-dried cypress sawdust without oil and impurity as the carbon source raw material. Dry the sawdust at 105 °C for 12 h to remove the free moisture in the raw material. Then use a high-speed pulverizer to crush it into fine powder, and then screen it with a standard sieve. Retain the part with a particle size less than 180 μm (about 80 mesh) for standby; wash it with deionized water multiple times until the pH of the washing liquid is stable at 7. Finally, vacuum dry the obtained solid sample at 80 °C for 12 h to obtain the target product, which is biochar (denoted as MB).

[0079] Performance Test

[0080] The biochar materials prepared in Examples 1-2 and Comparative Examples 1-2 were analyzed to obtain the N2 adsorption-desorption isotherm diagram. The results are shown in Figure 1 ( Figure 1 The adsorption and desorption branches are drawn simultaneously. In the BET adsorption isotherm experiment, first adsorb, then desorb, and the micropore segments basically coincide, and the mesopore segment shows a hysteresis loop. P / P0 < 0.1: The micropore adsorption is almost reversible, and the adsorption and desorption points coincide highly, so the lines overlap. 0.4 < P / P0 < 0.9: If the sample contains mesopores / slit pores, a typical H3 / H4 type hysteresis loop will appear; at this time, the adsorption amount cannot immediately return to its original position during the pressure reduction process, and the desorption branch is lower than the adsorption branch.). According to Figure 1The test results show that, with the exception of the comparative sample (MB) without phosphoric acid, all other phosphorus-doped samples exhibit typical mixed Type I and Type IV nitrogen adsorption-desorption isotherms, indicating that the prepared samples possess both distinct microporous and mesoporous structures, exhibiting a typical multi-level pore distribution. In the low relative pressure region (P / P0 < 0.1), the adsorption capacity increases rapidly, indicating that the microporous structure is well-developed and that micropores dominate the adsorption sites. In the intermediate relative pressure range (0.1 < P / P0 < 0.9), the adsorption curve plateaus, further confirming that microporous adsorption is the primary mechanism. Furthermore, an H4-type hysteresis loop appears in the P / P0 > 0.4 region, a hysteresis morphology typically associated with lamellar stacking structures and slit-type pores. Furthermore, in the high relative pressure region (P / P0 > 0.9), the adsorption capacity increases sharply, reflecting the presence of a certain proportion of macroporous structures. The above isotherm characteristics collectively demonstrate that the samples prepared by the present invention possess a typical hierarchical pore structure composed of ultramicropores, micropores, mesopores, and some macropores. Further analysis of the effect of different hydrothermal carbonization temperatures on the pore structure reveals that (MBP2-200-A and MBP2-240-A) the inflection point of the sample adsorption curve gradually shifts upward as the temperature increases from 200°C to 240°C, indicating that the heating process promotes the development and formation of micropores. The effect of the phosphoric acid addition ratio on pore structure evolution exhibits a somewhat nonlinear response: when the phosphoric acid mass ratio is controlled at the level of Example 1, the pore structure is significantly optimized, as evidenced by a significant upward shift in the inflection point of the adsorption curve, and a simultaneous increase in pore volume and specific surface area. However, when the phosphoric acid addition level is further increased to 110 mL (MBP3-240-A, as in Comparative Example 1), the adsorption curve slightly decreases, and the pore size distribution peak also shifts downward, indicating that excessive phosphoric acid may cause localized destruction of the carbon framework or pore collapse, thereby adversely affecting the stability of the porous structure. As a comparison, the MB sample showed extremely low adsorption capacity and essentially no effective pore structure, indicating that it was difficult to effectively adsorb gaseous pollutants. This phenomenon further demonstrates the key role of the synergistic regulation strategy of phosphorus doping and chemical activation in the present invention in constructing a reasonable pore structure.

[0081] The relevant pore structure parameters of the embodiments and comparative examples are detailed in Table 1.

[0082] Table 1 Pore structure parameters of examples and comparative examples

[0083]

[0084] Combined with Table 1 and Figure 1As can be seen, the present invention proposes a method for preparing phosphorus-doped, hydrothermally activated, hierarchically porous green biochar, involving a ternary coupled control mechanism of "in-situ phosphoric acid doping + hydrothermal carbonization + chemical activation." Compared to the common "carbonization + separate activation" or "pre-doping + carbonization" routes in the prior art, this method introduces phosphoric acid as a structural modulator and functional doping source during the initial carbonization phase, enabling in-situ phosphorus doping and high dispersion during carbon structure formation, significantly different from post-treatment phosphorus doping routes. Furthermore, the present invention explicitly proposes for the first time the nonlinear regulation of pore structure evolution by phosphoric acid addition ratio and hydrothermal temperature, enabling the coordinated construction of a hierarchical pore structure (micropores, mesopores, and macropores). The process is mild and simple to operate, using inexpensive and readily available raw materials such as sawdust, phosphoric acid, and KOH. The overall preparation process does not require the use of toxic reagents or high-pressure equipment, resulting in high safety and minimal environmental impact. The resulting biochar material is structurally stable and exhibits excellent regeneration performance. It has demonstrated excellent adsorption capacity and penetration for formaldehyde pollutants at room temperature.

[0085] Formaldehyde adsorption experiment

[0086] Dynamic breakthrough curve experiment is a direct and effective method to evaluate the adsorption performance of formaldehyde (HCHO) by phosphorus-doped porous biochar. Figure 2 The HCHO breakthrough curves of the biochar materials of Examples 1-2 and Comparative Examples 1-2 were measured under dry conditions at 25°C. The adsorption capacity q (mmol / g) was calculated using the following formula:

[0087]

[0088] Where F is the intake volume flow rate, m is the mass of the adsorbent, C0 is the initial concentration of formaldehyde at the intake end, C t is the formaldehyde concentration at the outlet at time t, t is the time, t sat The curve reaches C0 / C t (correspond Figure 2 The time when C / C0)=1.

[0089] Among the four test samples of Examples 1-2 and Comparative Examples 1-2, MBP2-240-A showed the best breakthrough curve characteristics: its C0 / C t It can be maintained below 0.05 for about 65 minutes, and it does not gradually rise to 1 until 160 minutes, so the shaded area under the curve is the largest, and the formaldehyde adsorption capacity obtained by integration conversion is as high as 8.75mmol / g. In contrast, the curve of MBP3-240-A rises earlier, the shaded area shrinks, and the corresponding capacity is about 6-7mmol / g; MBP2-200-A breaks through again in advance, and its capacity is about 5-6mmol / g. The undoped and KOH-unactivated matrix sample MB reaches C0 / C0 almost at the beginning of the experiment. t≈1, the shadow area is the smallest, and the adsorption capacity is less than 0.5mmol / g. In summary, it is precisely because of the synergistic effect of phosphorus doping and KOH activation that the adsorption time of low C0 / C t phase, thus obtaining the largest integrated area and the highest adsorption capacity. This indicates that the synergistic effect of phosphorus doping and KOH activation plays a key role in improving the HCHO adsorption efficiency.

[0090] By calculating the adsorption capacity using the above scheme, it can be found that the HCHO adsorption capacity of different samples in the examples and comparative examples is significantly different, among which the adsorption capacity of the MBP2-240-A sample is the highest, reaching 8.75mmol / g. Further analysis shows that as the hydrothermal carbonization temperature increases from 200℃ to 240℃ (MBP2-200-A→MBP2-240-A), the adsorption performance of the material is significantly enhanced. However, when the phosphoric acid addition ratio is further increased to 1:11 (MBP3-240-A), the adsorption performance decreases. Further combined with Figure 1 The pore structure analysis shows that MBP2-240-A has the best micropore structure (pore size <1nm), indicating that under this condition, the hydrothermal carbonization and KOH activation processes achieve a synergistic effect of structural optimization.

[0091] Therefore, the technical solution of the present invention is able to achieve efficient adsorption of formaldehyde. It is necessary to precisely control the hydrothermal temperature and the phosphoric acid doping ratio to achieve synergistic optimization of pore structure development and introduction of phosphorus functional groups.

[0092] The above are only preferred specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or replacements that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.

Claims

1. A method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar, characterized in that: The following steps are involved: The biomass raw material is mixed with a phosphoric acid catalyst to carry out a hydrothermal carbonization reaction. After the reaction is completed, the reaction product is separated into solid and liquid. The solid phase material is collected, dried, and then mixed with potassium hydroxide for activation treatment. The obtained product is washed and dried to obtain the phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar.

2. The method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar according to claim 1, characterized in that: The mass ratio of the biomass raw material to the phosphoric acid catalyst is 1:

9.

3. The method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar according to claim 2, characterized in that: The concentration of the phosphoric acid catalyst is 1 mol / L.

4. The method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar according to claim 1, characterized in that: The reaction temperature of the hydrothermal carbonization reaction is 200-240° C., and the reaction time is 2 hours.

5. The method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar according to claim 4, characterized in that: The hydrothermal carbonization reaction was carried out under a nitrogen atmosphere at a flow rate of 60 mL / min.

6. The method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar according to claim 1, characterized in that: The mass ratio of the potassium hydroxide to the solid phase material is 1:

3.

7. The method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar according to claim 1, characterized in that: The activation treatment is as follows: heating to 700° C. at a heating rate of 5° C. / min and reacting at this temperature for 2 hours.

8. The method for preparing phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar according to claim 7, characterized in that: The activation treatment was carried out under a nitrogen atmosphere at a flow rate of 60 mL / min.

9. A phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the phosphorus-doped hydrothermal synchronously activated multi-level porous green biochar as claimed in claim 9 in formaldehyde adsorption.

Citation Information

Patent Citations

  • Sulfur and phosphorus doped biomass porous carbon material and preparation method thereof

    CN113428855A

  • Phosphorus-doped porous carbon material and preparation method and application thereof

    CN115231546A

  • Formaldehyde-removing odor-inhibiting air purifying agent and preparation method thereof

    CN118925672A

  • Activated carbon, hydrochar and processes for making same

    WO2016072932A1

Cited By

  • Gradient aperture activated carbon for adsorbing formaldehyde-benzene series and preparation method of gradient aperture activated carbon

    CN121490731A

  • A gradient pore activated carbon for adsorbing formaldehyde-benzene series and a preparation method thereof

    CN121490731B